2002
DOI: 10.1289/ehp.0211015
|View full text |Cite
|
Sign up to set email alerts
|

Dioxins and endometriosis: a plausible hypothesis.

Abstract: A potential connection exists between exposure to organochlorine chemicals and the increasing prevalence of endometriosis. Evidence shows that dioxin (2,3,7,8-tetrachlorodibenzo-p-dioxin) can increase the incidence and severity of the disease in monkeys and can promote the growth or survival of endometrial tissue implanted into rodents in a surgically induced model of endometriosis. The mechanism of the connection between organochlorine chemicals and endometriosis is not clear. Effects on growth factors, cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 54 publications
(53 reference statements)
0
50
0
3
Order By: Relevance
“…Environmental toxins, including dioxin, have been implicated as risk factors of endometriosis [29]. It was stated that phase I drug-metabolizing enzymes (DMEs) metabolized toxic compounds to genotoxic electrophilic intermediates, and phase II DMEs conjugate the intermediates to water-soluble deriva tives, completing the detoxification cycle [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental toxins, including dioxin, have been implicated as risk factors of endometriosis [29]. It was stated that phase I drug-metabolizing enzymes (DMEs) metabolized toxic compounds to genotoxic electrophilic intermediates, and phase II DMEs conjugate the intermediates to water-soluble deriva tives, completing the detoxification cycle [30].…”
Section: Discussionmentioning
confidence: 99%
“…The products of CYP1A1 are involved in estrogen and PAH metabolism. It was shown that CYP1A1 was involved in metabolism of dioxin, which may increase the incidence and severity of endometriosis in monkeys [29]. Moreover, CYP1A1 is also involved in estrogen metabolism, catalyzing the hydroxylation of 17β-estradiol at the C-2 position [31].…”
Section: Discussionmentioning
confidence: 99%
“…These alterations may induce endometriosis or cancer by altering a dioxininduced oestrogen growth signal. Dioxins are environmental contaminants, and have been shown to induce endometriosis-like and oestrogen-dependent tumours in animal models (Birnbaum & Cummings 2002). Of importance, there is a doubled risk of developing endometriosis amongst women with high serum dioxin levels (Eskenazi et al 2002).…”
Section: Self-sufficiency In Growth Signalsmentioning
confidence: 99%
“…Like sporadic cancer (Balmain et al 2003), endometriosis may be considered to arise by complex interactions between inherited germline polygenic low-penetrance alleles (polymorphisms) (Hadfield et al 2001, somatically acquired genetic alterations , environmental factors (Birnbaum & Cummings 2002), and the processes of the hallmarks of cancer described earlier.…”
Section: Implications Of the 'Endometriosis Is A Neoplastic Process' mentioning
confidence: 99%
“…Moreover, estrogens seem to be involved in maintaining the male skeleton (11). Thus one possible hypothesis is that dioxins or other POC act as endocrine disruptors and modulate the homeostasis of estrogens or other steroid hormone systems (12).…”
mentioning
confidence: 99%